DISHONESTY IN THE IVORY TOWER: EXAMINATION CHEATING AND CORRUPTION IN HIGHER EDUCATION - Kaur, Amandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Higher education institutions are meant to be bastions of knowledge, integrity, and the development of ethical leaders. However, a pervasive issue of dishonesty, manifesting as examination cheating and broader corruption, threatens to undermine the very foundations of these institutions. This paper explores the multifaceted problem of dishonesty in higher education, examining its various forms, underlying causes, detrimental consequences, and potential strategies for mitigation. By analyzing the prevalence of examination cheating and the insidious nature of corruption within educational systems, this research aims to shed light on the urgency of addressing these issues to safeguard the credibility and societal impact of higher education.